Synthesis and Evaluation of Technetium-99m-Labeled pH (Low) Insertion Peptide Variant 7 for Early Diagnosis of MDA-MB-231 Triple-Negative Breast Cancer by Targeting the Tumor Microenvironment - Chen, Yuehua; Su, Yuan; Pang, Xufeng; Song, Xiaoxia; Zhao, Wanjun; Yu, Mingming (Frontiers in Oncology, 2022)
Objective To prepare technetium-99m (99mTc)-labeled pH (low) insertion peptide variant 7 [pHLIP (Var7)] and carry out small-animal single-photon-emission computed tomography (SPECT)/computed tomography (CT) imaging of tumor-bearing nude mice in vivo to study its value in the early diagnosis of triple-negative breast cancer (TNBC). Methods The pHLIP (Var7) sequence was synthesized via solid-phase peptide synthesis. Four amino acids, Gly-(D)-Ala-Gly-Gly, were attached to the N-terminus of pHLIP (Var7) to form a strong chelating group containing an N4 structure. The peptide was labeled with 99mTc using a direct labeling method. We determined the in vitro binding fraction of 99mTc-pHLIP (Var7) to MDA-MB-231 cells. Serial biodistribution studies and small-animal SPECT/CT imaging in MDA-MB-231 TNBC-bearing mice were performed using 99mTc-pHLIP (Var7). Results The radiochemical yield and purity of 99mTc-pHLIP (Var7) were 99.49 ± 0.17% and 99.63 ± 0.44%, respectively. The radiochemical purity was still more than 96% after 24 h in serum. The binding fraction of 99mTc-pHLIP (Var7) to MDA-MB-231 cells continuously increased in an acidic environment and was significantly higher than the cell-binding fraction (P < 0.01) at pH = 7.4 and the cell-binding fraction (P < 0.01) of 99mTc-kVar7 at different pH values (pH = 6.0, 6.5, 7.0 and 7.4) at each time point (P < 0.01). The distribution of 99mTc-pHLIP (Var7) in tumors at each time point was significantly greater than that of 99mTc-kVar7 (P < 0.01). SPECT/CT imaging was largely consistent with the biodistribution results; the tumor was clearly imaged at each time point after injection of 99mTc-pHLIP (Var7) but could not be imaged after injection of 99mTc-kVar7. Conclusion 99mTc-pHLIP (Var7) showed a high radiochemical yield and stability and was highly concentrated in tumor tissues. Although there was strong radioactive background in the abdomen of tumor-bearing nude mice, it did not hinder early diagnosis of TNBC.